The use of freeze-dry bovine pericardium (FDBP) in diaphragmatic herniorrhaphy in dogs - Mohamad Yusof, Loqman; Wong, C. M.; Bejo, Mohd Hair; Abu Bakar @ Zakaria, Md Zuki; Yagoub Mohamed, Abdel Hafeez (Malaysian Medical Association, 2004)
A study was conducted to investigate the effectiveness of freeze dried bovine pericardium (FDBP) as a biomaterial in diaphragmatic herniorrhaphy in dogs. A total of 8 adult dogs were randomly selected and divided into 2 groups. In the FDBP group, a diaphragmatic defect was induced and repaired with an identical size of FDBP. In the control group, a diaphragmatic wall was incised at the 3-side border creating a flap and was sutured. Grossly, only mild intrathoracic adhesion was observed in most animals, and no herniation, occurred. Microscopically, the biomaterial incorporated into the host's tissue by in growth of young muscle fibres and massive new blood vessel formation in between the fibrous tissue.